Exploitation of agro-industrial wastes: Chemical and physical treatments of coconut fibers with potential use in composite materials - Argote Ortiz , Eduardo; Alban Bolaños , Pedro; Cajiao Buitrón , Elsa Susana; Villada Castillo, Héctor Samuel (I+ T+ C- Research, Technology and Science, 2024)
The growing demand for plastics and their poor end-of-life management has prompted the search for sustainable alternatives, such as natural fiber-reinforced composites. Fibers, such as coconut fibers, have been shown to improve these compounds’ properties significantly. In this study, natural coir fibers (NCF) treated with different chemical and physical processes, such as sodium hydroxide (NaOH), sodium hypochlorite (NaOCl), and ultrasound (U), were analyzed. Structural, morphological and water absorption properties were tested by infrared spectroscopy, water absorption and X-ray diffraction tests. These indicated that treated fibers show a decrease or loss of transmittance bands associated with lignin, hemicellulose and a higher concentration of cellulose bands. Thus, higher water absorption and an increase in the crystallinity index were observed, which enhances its reinforcing capacity and improves the interaction between a polymeric matrix and the fibers. It also highlights the potential for the use of agroindustrial waste under a circular economy approach, promoting its incorporation into new sustainable products.